Perspective Role of the Greater Eurasian Partner in the System of International Relations - Roman I. Anferov (Евразийская интеграция: экономика, право, политика, 2019)
This article explores the perspective role of the Eurasian Economic Partnership in the formation of modern international integration institutions. The settlement of contentious issues arising during this process. In addition, the article examines the legal framework for the activities of a number of integration associations, taking into account the aspect of the formation of their legal personality. The author has considered the recession in the role of a number of international institutions, as well as the events of our time, directly indicating the possibility of predicting the development of integration processes.Conclusion: The idea of the Great Eurasia will capture an increasing number of states and it is possible that a new global legal institution will be created on the world stage linking the states of Europe and Asia. The development of a preferential trade zone and more advanced stages of international integration based on the activities of already existing international institutions will be accelerate over time.